Population Status of Cacatua sulphurea parvula and Trichoglossus euteles in Alor, East Nusa Tenggara (Biodiversitas Journal of Biological Diversity, 2009)
The aim of this survey was to know the abundance status of the Yellow-crested Small Cockatoo (Cacatua sulphurea parvula) and Yellow-headed Lorikeet (Trichoglossus euteles) in Alor, East Nusa Tenggara Province. There were four observation sites in the survey, namely: (i) Air Mancur preparatory Village (in and around of Tuti Adigae Natural Tourism Park, East Alor Sub-district), (ii) Tanglapui Village (Kampong Irawuri) (East Alor Sub-district), (iii) Probur Village (Kampong Wormanem) (Southwest Alor Sub-district), and (iv) Bota Village (Northwest Alor Sub-district). The survey was used for the bird encounter rates per unit time method. The bird population was estimated by abundance score value. Fifty species of birds or 64.9% of 77 species of birds occurring in Alor were recorded during field work. The yellow-headed lorikeet observed was more abundant with five abundance score and for the numbers per 10 hours observation were 58.06. There was no yellow-crested small cockatoo observed during the survey. However, the yellow-crested small cockatoo was presumed to be present in the fields by the direct observation of old nest site of Canarium trees.Key words: parrot, population, Cacatua sulphurea parvula, Trichoglossus euteles, Alor